Maghi: The Festival Among The Tharus: Celebration of New Year (Patan Pragya, 2019)
Nepal incorporates diversity of caste, ethnicity, language, social structure, culture and religion, among which Tharus are one of the indigenous groups of the Tarai and inner Tarai region of the country. The study is dedicated to explore the practice and process of celebrating Maghi as Tharunew year. This study has been conducted by employing both exploratory and descriptive research design. The data of the present article are based on published articles and books and on interviews with the elders of the Dangaura Tharus, ritual performers and educated persons of the community. This study represents the distinct socio-cultural structure and ethnic practice of Dangaura Tharu. Indigenous festivals are significant in anthropological research. So it helps to add specific knowledge about Maghi, the indigenous festival of Tharu people. But the central aspect of the celebration of Maghi is in the verge of gradual change. Because those characters which are not suitable for today is going to be abolished and those that are suitable are carried on continuously. Some factors that are core components cannot be changed and it is continuous even though they do not bear any meaning but continue in the respect of their fore ancestors.